Reference interval and preanalytical properties of serum neurofilament light chain in Scandinavian adults. (1st July 2020) - Hviid, Claus Vinter Bødker; Knudsen, Cindy Soendersoe; Parkner, Tina
Abstract: The neurofilament light chain (NfL) is a promising biomarker of neuronal injury which is approaching routine clinical use. With the development of ultra-sensitive technologies, NfL has become measurable in the peripheral blood but the reference interval for serum NfL remains to be established. NfL was measured by a single-molecule array (Simoa™) analysis under internal and external quality control which is established for routine clinical use. Serum samples from 342 reference subjects, 18−87 years were analyzed. The age-partitioned reference interval was established according to Clinical and Laboratory Standards Institute guidelines, an approximation of the upper reference interval limit per 10-year age-groups was performed, and key pre-analytical properties were examined. Serum NfL levels increased 2.9% per year. The non-parametric reference interval for the age groups 18−40, 41−65, and >65 years were 2.8−9.7 ng/L, 4.6 − 21.4 ng/L, and 7.5−53.8 ng/L, respectively. The estimated upper reference interval limits per 10-year intervals corresponded well with the 90% confidence limits of the non-parametric reference interval. The recovery of serum NfL after seven days at room temperature or three freeze-thaw cycles were 93% (95% CI: 89%−97%) and 92% (95% CI: 83%−102%) and levels in serum were only slightly higher than levels in plasma ( p < .0001). The study establishes the serum NfL reference interval, provide estimated upper reference intevral limits in 10-year intervals to increase the clinical applicability and uncover pre-analytical properties that make serum NfL feasible for clinical use.